ReGen Hall: A Scalable Model for Environmentally Sustainable, Affordable, and Compatible Student Housing - Abdolshahi, Saba (Enquiry The ARCC Journal for Architectural Research, 2025)
Affordability is one of the most important factors in student housing development, especially in rapidly growing cities with increasing property prices. Beyond economic aspects, student housing needs to focus on environmental issues and community integration to create and maintain sustainability in the long run. ReGen Hall illustrates a unique approach to student housing projects aiming to demonstrate the viability of integrating ecological sustainability and affordability while preserving the community fabric. Located in Austin, Texas, the project incorporates advanced modular construction methods, Passive House design principles, and innovative net-zero energy strategies. This 62,000-square-foot residence hall integrates renewable energy systems, including a 320-kW photovoltaic array and rainwater harvesting infrastructure, to significantly reduce operational emissions and water dependency. Life Cycle Analysis (LCA) of the building carried out over a projected lifespan of 100 years reveals a carbon footprint of 2,853 tons of CO2e. This analysis is calculated using verified data from One Click LCA and industry benchmarks to ensure rigorous methods. Economic evaluations show cost reductions through modular construction, bringing total project expenses well below local benchmarks. Moreover, community-focused design elements, such as shared spaces, green courtyards, and a free medical clinic, foster social cohesion while meeting the housing needs of a diverse student population. Employing a quantitative research approach and spatial analysis, this study evaluates the environmental, economic, and social impacts of ReGen Hall. The findings demonstrate that sustainable technologies can effectively balance affordability and environmental stewardship and offer a model for future student housing developments.